2013
DOI: 10.1002/app.39103
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and surface modification of electrospun aligned poly(butylene carbonate) nanofibers

Abstract: In this study, aligned poly(butylene carbonate) nanofibers were fabricated by electrospinning with a high‐speed transfer roller as the receiving device. Cold plasma treatment technology was applied to improve its hydrophilicity and activity to expand its application in biological materials. The morphology of the fibers was investigated with scanning electron microscopy. X‐ray diffraction was used to research the impact of the rotation speed on the crystallization and orientation degree of the crystals. The ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…. The water contact angle of PBCU is about 104.9°, which shows that PBC is a typical hydrophobic material . Nevertheless, with the PESe segment content increasing, the water contact angle of PBC‐PESe1–4 decline from 89.2 to 80.5 o , which indicate that the hydrophilicity of PBC‐PESe improves along with the increasing content of incorporating PESe segment.…”
Section: Resultsmentioning
confidence: 97%
“…. The water contact angle of PBCU is about 104.9°, which shows that PBC is a typical hydrophobic material . Nevertheless, with the PESe segment content increasing, the water contact angle of PBC‐PESe1–4 decline from 89.2 to 80.5 o , which indicate that the hydrophilicity of PBC‐PESe improves along with the increasing content of incorporating PESe segment.…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, the surface modification of synthetic biomaterials with the intent to improve biocompatibility has been extensively studied. Many common techniques, such as plasma treatment [208][209][210] and gradients, 211 can be considered for the modification of aligned electrospun nanofibers. For instance, electrospun aligned poly(propylene carbonate) (PPC) microfibers were treated with oxygen plasma and chitosan nanofibers were introduced by freeze drying.…”
Section: Discussionmentioning
confidence: 99%
“…136 Another pathway to graft peptides onto the surface of nanofibers by plasma is without the use of coupling agent according to a supposed mechanism detailed in Figure 13c. 138,144 It is important to note that the plasma gas used influences the procedure. Indeed, for direct coupling, O 2 and CO 2 are favored to create carboxylic acid functions.…”
Section: Cold Plasma Treatment Of Electrospunmentioning
confidence: 99%
“…Finally, Shao et al reported the low-pressure helium plasma treatment of poly(butylene carbonate) (PBC) nanofibers to graft gelatin, through polymer grafting without coupling, 144 and found that for a plasma power comprised between 20 and 80 W, the contact angle decreased rapidly and the absorption rate of the drop quickly increased. However, for a plasma power higher than 100 W, these characteristic rates started to decrease.…”
Section: Cold Plasma Treatment Of Electrospunmentioning
confidence: 99%